2017
DOI: 10.1002/jcp.26202
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of miR‐23a from hypoxic tumor cell colonies can induce angiogenesis

Abstract: Neo vessel formation by angiogenesis is an important event during many pathological conditions including cancer, where it is indispensable for tumor growth and survival. Although, various pro-angiogenic cytokines and soluble factors, secreted by tumor cells, have been reported to promote angiogenesis, recent studies have shown regulatory role of exosomes, secreted by tumor cells in the process of angiogenesis. These exosomes are capable of carrying nucleic acids, proteins, etc., as their cargo. Under the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Further, report from our group suggests that miR-106a regulates the expression of MMP9 during cell migration by directly targeting SIRT1 mRNA (151). Our group has also reported that the horizontal transfer of miR-23a from tumor cell colonies can induces angiogenesis by targeting SIRT1 in the recipient endothelial cells (152). Further, miR-212 has been reported to exhibit anti-angiogenic properties, by targeting SIRT1 and Gab1 in endothelial cells (153).…”
Section: Post Transcriptional Regulation Of Sirtuins: Importance Of Mmentioning
confidence: 84%
“…Further, report from our group suggests that miR-106a regulates the expression of MMP9 during cell migration by directly targeting SIRT1 mRNA (151). Our group has also reported that the horizontal transfer of miR-23a from tumor cell colonies can induces angiogenesis by targeting SIRT1 in the recipient endothelial cells (152). Further, miR-212 has been reported to exhibit anti-angiogenic properties, by targeting SIRT1 and Gab1 in endothelial cells (153).…”
Section: Post Transcriptional Regulation Of Sirtuins: Importance Of Mmentioning
confidence: 84%
“…Studies have shown that miR-23a can be carried by tumor cell-secreted exosomes such as nasopharyngeal carcinoma or lung cancer cells and then exert their regulatory functions on angiogenesis (22)(23)(24), which suggested that miR-23a carried by GC cell-derived exosomes might be involved in angiogenesis. To validate this hypothesis, exosomes were extracted from GES-1, NCI-N87, HGC-27, AGS, and MKN45 using the ExoQuick method and then identified.…”
Section: Mir-23a Is Enriched In Gc Cells-derived Exosomesmentioning
confidence: 99%
“…30 Recent studies from our group have substantiated the importance miR-23a among other cluster members, as it is significantly up regulated in exosomes secreted by hypoxic tumor cells colonies and horizontal transfer of which induced angiogenesis in the recipient endothelial cells. 40 Interestingly, the in silico analysis using online tools at miRBase suggested that miR-23a has got target site on the 3′ UTR of LDH A and LDH B mRNAs ( Figure 3A(1-3)). So, we went on to check the role of miR-23a if any, in regulating LDH expression during ER stress.…”
Section: Discussionmentioning
confidence: 99%